(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2015)
In previous papers [Sinha and Bhatia, Phys. Rev. A 83, 063417 (2011), and Bhatia and Sinha, Phys. Rev. A 86, 053421 (2012)] cross sections for the freefree transitions are calculated for a low energy (external) electron hydrogen scattering in the presence of an external homogeneous, monochromatic, and linearly polarized laser field, without and with the presence of plasma screening, respectively. The present calculation is extended to hydrogenic systems with nuclear charge greater than one. The Debye-Hückel approximation is used to investigate the effect of plasma screening. Calculations are carried out in the soft photon limit. The incident electron is considered to be dressed by the laser field non-perturbatively by choosing the Volkov solutions in both the initial and final states. The scattering wave function for the electron is obtained in the exchange approximation. The laserassisted differential and total cross sections are calculated for single photon emission or absorption and no photon-exchange in the soft-photon limit, the laser intensity being much less than the atomic field intensity. The calculations have been carried out for various values of Debye parameter μ, ranging from 0.08 to 0.30. A strong suppression is noted for the laser-assisted singlet and triplet cross sections compared to the field-free situation. The suppression depends on μ, state of the system as well as on the incident electron momentum. This is unlike in the case of the hydrogen atom in the laser field where the suppression was much more for the triplet cross sections compared to the field-free situation.